Information and Communications Technology (ICT) Tools that Support Access to the Labor Market of People with Visual Functional Diversity - Ortiz-Clavijo, Luis Felipe; Giraldo Gutiérrez, Francisco Luis (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2020)
This manuscript is derived from an investigative exercise that forms part of the theoretical sustenance in the development of a master thesis, with the objective of evaluating the implementation of a governmental project oriented to train in the use and appropriation of technological tools by the population with visual functional diversity in Colombia. In this article, show various theoretical positions based since the science, technology and society studies, accessibility and functional diversity. Finally, a synthesis is made from the STS studies and the disability models.